What Wounds Enable: The Politics of Disability and Violence in Chicago - Ralph, Laurence (Disability Studies Quarterly, 2012)
This paper is about what wounds reveal about the diversity among stigmatized groups. My argument is that the focus on mitigating social difference within the disability rights movement has inadvertently served to obscure key distinctions among disabled populations. As evidence for my thesis, I focus this paper on anti-gang forums hosted by disabled ex-gang members. Examining these forums ethnographically—and investigating the argument made by disabled, ex-gang members that their wounds enable them to save lives—allows me to describe some of the contexts in which it becomes politically strategic to inhabit the role of a "defective body" in order to make claims about a violent society.